THE IMPLEMENTATION OF ACCOUNTING SYSTEM ON RAW MATERIALS IN ORDER TO SUPPORT THE INTERNAL CONTROL (Case study at Tiara Handicraft Surabaya) - Ade Liana Fajrin; . Kertahadi; Siti Ragil Handayani (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
Penelitian ini bertujuan untuk: mengidentifikasi kunci keberhasilan dalam operasi bisnis perusahaan, untuk menggambarkan implementasi system akuntansi pada bahan baku untuk menunjang pengendalian internal yang telah diterapkan oleh Tiara Handicraft, meskipun terdapat beberapa kelemahan seperti fungsi ganda di beberapa departemen, merekam setiap transaksi ke dalam catatan akuntansi yang dilakukan setelah pembayaran dan proses pemesanan. Tiara Handicraft adalah perusahaan Usaha Kecil dan Menengah (UKM) yang memiliki penilaian tinggi dalam produknya. Dengan menerapkan sistem yang baik, perusahaan dapat melakukan rencana pengawasan, pengendalian, dan aktivitas yang berhubungan dengan pembelian bahan baku. Tiara Handicraft harus menerapkan pelaksanaan sistem akuntansi bahan baku dengan baik dan memadai. Oleh karena itu, dapat disarankan untuk memperbaiki prosedur pencatatan dan memperbaiki system organisasi untuk meningkatkan pengendalian intern dalam perusahaan. Kata Kunci: Accounting system of raw materials, internal control, purchasing raw material, system and procedure, accounting system. ABSTRACT These research objectives are to: identify the key success in business operations of the company, to describe the implementation of accounting system on raw materials in order to support the internal control that has been applied by Tiara Handicraft, although there are shortcomings such as the dual function in a several department, recording every transaction into the accounting records made after payment and process order. Tiara Handicraft Company is the Small and Medium Enterprises (SMEs) which is have a high demand in their product. By applying a good system, the company can conduct supervision, control, and activity plan which is associated with raw materials supply. Tiara Handicraft Company must apply the implementation of raw materials accounting system well and adequately. Therefore it can be suggested to improve their record-keeping procedures, and improving organizational systems in order to improve the internal control in the company. Keywords: Accounting system of raw materials, internal control, purchasing raw material, system and procedure, accounting system.